In‐depth molecular profiling of the biphasic components of uterine carcinosarcomas. (9th April 2015) - McConechy, Melissa K; Hoang, Lien N; Chui, Michael Herman; Senz, Janine; Yang, Winnie; Rozenberg, Nirit; Mackenzie, Robertson; McAlpine, Jessica N; Huntsman, David G; Clarke, Blaise A; Gilks, Cyril Blake; Lee, Cheng‐Han
Abstract Uterine carcinosarcoma is a clinically aggressive malignancy composed of a mix of carcinomatous and sarcomatous elements. We performed targeted next‐generation sequencing of 27 uterine cancer and sarcoma genes together with immunohistochemical analyses of selected proteins in 30 uterine carcinosarcomas. This included 13 cases in which the distinct carcinoma and sarcoma components were sequenced separately and 10 cases where the metastatic tumours were analysed in addition to the primary tumours. We identified non‐synonymous somatic mutations in 90% of the cases, with 27 of 30 cases (90%) harbouring TP53 alterations. The PI3K pathway was the most commonly mutated signalling pathway with mutations identified in PIK3CA, PTEN, PIK3R1, and/or PIK3R2 in two‐thirds of the cases. Mutations in FBXW7, PPP2R1A, ARID1A and KRAS were demonstrated in a minority of cases. In cases where the carcinomatous and sarcomatous components were separately analysed, most of the mutations identified were present in both components, indicating a common origin for the two components. Furthermore, the same TP53 alterations and/or PI3K pathway mutations seen in the primary tumours were also identified in the metastatic sites. Overall, carcinosarcomas exhibited heterogeneous molecular features that resemble the heterogeneity seen in endometrial carcinomas, with some showing endometrioid carcinoma‐like and others showing serous carcinoma‐like mutation profiles. While patients with serous‐like tumours presented more frequently with advanced‐stage disease compared to patients with endometrioid‐like tumours, there was no statistical difference in outcome between the two groups. Our results provide insights into the oncogenesis of uterine carcinosarcoma and identify targetable mutations that represent early oncogenic events. The findings of the different molecular types of uterine carcinosarcoma that parallel the different molecular types in endometrial carcinoma may have future treatment implications with targeted therapies.